1955
DOI: 10.1002/jsfa.2740060804
|View full text |Cite
|
Sign up to set email alerts
|

Moisture equilibrium of palm kernels

Abstract: Determinations have been made of the moisture contents of whole palm kernels kept for times up to 35 days in desiccators over saturated salt solutions for which the relative humidities a t 30' are known. The temperature fluctuated between 24' and 31".Factors which must be considered in the drying of foodstuffs are discussed. The conventional hot-air drying and the vacuum contact-plate drying methods are described and compared. The latter yields better dried products than the former, both in appearance and pala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The comparison between the two previous studies [11,13] showed important differences in the values of EMC; this difference might be as a result of differences in palm variety, the palm maturity, and EMC determination method [14]. The comparison between desorption isotherm of palm kernels published by Somade [74] and Jiménez et al [12] also showed important differences; Somade [74] obtained lower EMC values compared to Jiménez et al [12], whereby the difference was about 1.8% for the 75% RH. Jiménez et al [12] concluded that the observed differences in EMC values between the studies most likely were originated from the different genetic compositions of kernels used as well as the postharvest handling of the materials; another possible reason to explain these differences is the MC and RH determination techniques used, which were different in both studies.…”
Section: Fitting Of Sorption Modelsmentioning
confidence: 84%
“…The comparison between the two previous studies [11,13] showed important differences in the values of EMC; this difference might be as a result of differences in palm variety, the palm maturity, and EMC determination method [14]. The comparison between desorption isotherm of palm kernels published by Somade [74] and Jiménez et al [12] also showed important differences; Somade [74] obtained lower EMC values compared to Jiménez et al [12], whereby the difference was about 1.8% for the 75% RH. Jiménez et al [12] concluded that the observed differences in EMC values between the studies most likely were originated from the different genetic compositions of kernels used as well as the postharvest handling of the materials; another possible reason to explain these differences is the MC and RH determination techniques used, which were different in both studies.…”
Section: Fitting Of Sorption Modelsmentioning
confidence: 84%